SIRT1 inhibitory compounds from the roots of Codonopsis pilosula. Issue 1 (2nd January 2019) - Li, Xiao-Zhen; Cheng, Li-Zhi; Yan, Yong-Ming; Liu, Bao-Hua; Cheng, Yong-Xian
Abstract: Three new compounds, pilosulinene A (1 ), pilosulinols A (2 ), and B (3 ), along with seven known compounds, were isolated from the roots of Codonopsis pilosula cultivated in Xundian County of Yunnan Province . The structures of new compounds were established by spectroscopic methods. In particular, the presence of an aromatic ring in the structure of1 makes it intriguing. The inhibitory activity of compounds against SIRT1 was evaluated. The results showed that8 could inhibit Sirt1 in a dose-dependent manner. Abstract :